The effect of mobile application-based technology on post-stroke aphasia: a systematic review - Jiang, Zihui; He, Mingping; Zhang, Chenchen; Chen, Xiuen (Frontiers in Neurology, 2024)
Background: Enhancing speech-language therapy remains the most effective strategy for improving post-stroke aphasia, However, conventional face-to-face interventions often lack the necessary therapeutic intensity. In recent years, mobile application-based speech-language therapy has emerged progressively, offering new opportunities for independent rehabilitation among aphasic patients. This review aims to evaluate the impact of mobile application-based interventions on post-stroke aphasic. Methods: By conducting a systematic search across five databases (PubMed, Web of Science, EMBASE, CINAHL, and Scopus), we identified and included studies that investigated the utilization of mobile application-based technologies (such as computers, iPads, etc.) for treating post-stroke aphasia. Results: This study included 15 research investigations, including 10 randomized controlled trials (RCTs), 4 self-controlled studies and one cross-over experimental design study. Among these, 8 studies demonstrated the efficacy of mobile application-based therapy in enhancing overall language functionality for post-stroke aphasia patients, 3 studies highlighted its potential for improving communication skills, 3 studies observed its positive impact on spontaneous speech expression. Moreover, 4 studies indicated its effectiveness in enhancing naming abilities, 2 studies underscored the positive influence of mobile application-based interventions on the quality of life for individuals with aphasia. 6 studies noted that speech improvement effects were maintained during the follow-up period.The results of this review demonstrate the potential of mobile application-based interventions for improving speech-language function in individuals with aphasia. However, further high-quality research is needed to establish their effects across different domains and to delve into the comparative advantages of various treatment approaches.